The Impact of Talent Management, Knowledge Management, and Career Development on Employee Performance in the Banking Sector of Batam City: The Mediating Role of Motivation - Setyawan, Agustinus; Wildani, Lilian Nurul; Nelson, Alden (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to demonstrate the impact of Talent Management, Knowledge Management, and Career Development on Employee Performance in the banking sector of Batam City, with Motivation serving as a mediating variable. The research employs an observational analytical approach, utilizing a saturated sampling technique, which includes the entire population of 312 respondents as the sample. The analysis method used is Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The findings indicate that Employee Performance significantly influences the banking sector in Batam City. High motivation can enhance organizational commitment, and high scores in personality and motivation can further improve employee performance.